2022
DOI: 10.1038/s41421-022-00381-7
|View full text |Cite
|
Sign up to set email alerts
|

Broad ultra-potent neutralization of SARS-CoV-2 variants by monoclonal antibodies specific to the tip of RBD

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) continue to wreak havoc across the globe. Higher transmissibility and immunologic resistance of VOCs bring unprecedented challenges to epidemic extinguishment. Here we describe a monoclonal antibody, 2G1, that neutralizes all current VOCs and has surprising tolerance to mutations adjacent to or within its interaction epitope. Cryo-electron microscopy structure showed that 2G1 bound to the tip of receptor binding domain (RBD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…As expected, a strong correlation between minimal or no loss in body weight and undetectable lung virus load in the mice that received different doses of mAb combination was observed (Figs 7G and S12F ) . Taken together our study demonstrated significant protection by a combination of these two potently neutralizing mAbs at low dose against the highly virulent Delta variant in a transgenic hACE-2 mice model and was found to be comparable with few others tested against Delta variant [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 78%
“…As expected, a strong correlation between minimal or no loss in body weight and undetectable lung virus load in the mice that received different doses of mAb combination was observed (Figs 7G and S12F ) . Taken together our study demonstrated significant protection by a combination of these two potently neutralizing mAbs at low dose against the highly virulent Delta variant in a transgenic hACE-2 mice model and was found to be comparable with few others tested against Delta variant [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 78%
“…In our previous study 21 , we identified a broad-spectrum neutralizing antibody 2G1 that targets the tip of RBD through a small contact surface from our SARS-CoV-2 antibody repertoire, which makes it less possible in epitope clash with other antibodies and thus suitable for combinational use. We performed competition ELISA to map the epitope information of antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The VSV-SARS-CoV-2 broke through the protection of monotherapy by 9E12, 10D4 and 2G1 at the 9 th , 1 st and 4 th passages, respectively (Figure 2b). The emergency use authorization (EUA) antibody REGN10933, which has a similar epitope with 2G1, was used as a control 21 . The virus broken through REGN10933 at the 3 rd passage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations